Visible Spectrophotometric Methods for Estimation of Ketoprofen from Capsule Formulation - Singhavi, I.; Chaturvedi, S.C. (Asian Journal of Chemistry, 2010)
Two simple, sensitive and accurate extractive colorimetricmethods for estimation of ketoprofen from capsule formulation havebeen developed. Copper(II) acetate and copper(II) chloride were theanalytical reagents used for colour development. The methods arebased on the quantitative formation of coloured chloroform extractablecomplexes of drug with copper(II) ions. The complex formedusing copper acetate has an absorbance maxima at 676 nm andcomplex formed using copper(II) chloride showed absorbance maximaat 710 nm. For both methods Beer's law was obeyed in theconcentration range of 0-5 mg/mL. Results of analysis werevalidated statistically and by recovery studies.